A comparative analysis of perception levels of accuracy for indigenous weather forecasts and meteorological forecasts: The Case Of Wards 12 And 13, Mberengwa District, Zimbabwe - Shoko, K.; Shoko, N. (Midlands State University, 2014)
Residents of wards 12 and 13 in Mberengwa depend on subsistence agriculture for their livelihoods. These residents incorporate weather forecasts in agricultural decision-making especially in decisions that relate to crop production. The residents of the two wards have since developed their own indigenous weather forecasting systems that they use in conjunction with meteorological weather forecasts for agricultural planning purposes. This study examines the perceptions of the residents of wards 12 and 13 on the levels of accuracy of indigenous and meteorological weather forecasts. The data was collected using questionnaires and focus, group discussions. Purposive sampling was used to select the respondents. 66% of the respondents indicated that indigenous weather forecasts accuracy fell in the average to good rating while 59 % indicated that they rated meteorological weather forecasts as average to good . Comparative ratings of the accuracy of indigenous weather forecasts to meteorological weather forecasts showed that 91% of the respondents who had access to both meteorological and indigenous weather forecasts perceived the indigenous weather forecasts as being more reliable than meteorological weather forecasts. The study recommends an in-depth research of the indigenous weather forecasting systems so that the locals may fully benefit from this simple, inexpensive and easily accessible system of weather forecasting.